Nilai Peduli Sosial Dan Nilai Cinta Tanah Air Dalam Film Jembatan Pensil Produksi Grahandhika Visual - Luthfia Muqimatussunnah; Ika Ari Pratiwi; Su’ad Su’ad (Journal on Education, 2023)
Character values ​​are values ​​that are instilled in the character education of elementary school children as an effort to realize national education goals. Film is one of the media that can influence the character values ​​of children or each individual. This study aims to analyze the intrinsic structure of the film Jembatan Lilin, the value of social care and love for the homeland contained in the film Jembatan Pensil, produced by Grahandhika Visual. The type of research used in this study is a qualitative research with a descriptive approach. The data analysis that will be used is descriptive qualitative data analysis, namely data reduction, data presentation, and data verification. Data collection techniques in this research use documentation techniques and refer to records that are sourced from valid data. The research results in the film "Jembatan Pensil" contain four story structures which include themes, characters and characterizations, plot, setting, values ​​of social care and love of the country. The values ​​of social care contained in the film "Pencil Bridge" are mutual help, tolerance, tolerance, social action and noble character. The value of loving the motherland in the film "Jembatan Pensil" includes instilling nationalism, being proud of Indonesia, using the Indonesian language properly, and preserving Indonesian art and culture. The research implications are expected to have a positive impact on the audience, especially children.